UPAYA GURU DALAM MENERAPKAN METODE PEMBELAJARAN DIFERENSIENSI UNTUK SISWA BERKEMAMPUAN BERAGAM DIKELAS II SEKOLAH DASAR NEGERI 114/VII BUKIT KALIMAU ULU I KECAMATAN BATANG ASAI KABUPATEN SAROLANGUN - Siti Riamah; Sri Yulia Sari; Fitri Nauli Siagiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the efforts of teachers in implementing differentiated learning methods for students with diverse abilities in grade II at SDN 114/VII Bukit Kalimau Ulu I, Batang Asai District, Sarolangun Regency, and to identify the obstacles faced by teachers in implementing these methods. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects were the grade II teacher and students at SDN 114/VII Bukit Kalimau Ulu I. The results of the study show that the teacher's efforts in implementing differentiated learning methods are carried out in several ways, namely adjusting learning methods to students' abilities, providing variations of assignments according to the level of students' abilities, giving special attention to students who experience learning difficulties, and using various interesting learning strategies so that all students can participate well in the learning process. Teachers also strive to create a conducive learning atmosphere and provide motivation to students so that they are more active in the learning process. The obstacles faced by teachers in implementing differentiated learning include limited learning time, differences in students' abilities that are quite diverse, and limited supporting facilities and infrastructure. Nevertheless, teachers continue to make efforts to overcome these obstacles by providing additional guidance to students who need it and developing more varied learning strategies. Thus, the implementation of differentiated learning methods can help teachers accommodate differences in students' abilities so that the learning process can take place more effectively and optimally. Keywords: Teacher Efforts, Differentiated Learning, Diverse Student Abilities.